FOOD SAFETY AS ONE OF THE MAIN SAFETY P REOCCUPATIONS OF A MODERN MAN - Bjelajac, Željko; Dukić-Mijatović, Marijana; Dragojlović, Joko (Economics of Agriculture, 2017)
Industrialization, agricultural production and use of hormones, additives, pesticides, and like have influenced the increase in customers dissatisfaction, leading to loss of their confidence in institutions responsible for food safety control. It resulted in changes and adoption of more stringent legal regulations that followed the concept "from farm to fork" at the level of the European Union and the Republic of Serbia. It puts the emphasis on consumers and their right to have important facts for the proper selection of products (food) at their disposal. Consequently, the international standards which ensure the quality and safety of food are being developed. Therefore, the aim of this paper is to analyze food safety from the aspect of modern man through the methodological and theoretical framework. Analysis method will explain terms related to the food safety, while the normative method will be used to see legislation regulating the studying matter of food safety and consumer protection in the European Union and the Republic of Serbia, and the obtained results will be compared and summarized through comparative method.